36.2k views
25 votes
Rewrite the expression in a to the power of n form

Rewrite the expression in a to the power of n form-example-1
User Ali Nem
by
6.7k points

2 Answers

9 votes

Answer:


a^-7

Explanation:


(a^m)/(a^n)=a^((m-n)), then


(a^(-13) )/(a^(-6) )


=a^((-13-(-6)))


=a^((-13+6))


=a^(-7)

User Uniquenamehere
by
6.1k points
6 votes

Answer:


a^(-7)

Explanation:

using the rule of exponents


(a^(m) )/(a^(n) ) =
a^((m-n)) , then


(a^(-13) )/(a^(-6) )

=
a^((-13-(-6)))

=
a^((-13+6))

=
a^(-7)

User Aaron T Harris
by
6.1k points